Trypanosoma congolense in the microvasculature of the pituitary gland of experimentally infected Boran (Bos indicus) cattle - Abebe, G.; Shaw, M.K.; Eley, R.M. (SAGE Publications, 1993)
The pituitary glands of seven Boran cattle ( Bos indicus), five infected with a clone of Trypanosoma congolense IL 1180 (ILNat 3.1) transmitted by Glossina morsitans centralis and two uninfected controls, were examined by light and electron microscopy 43 (experiment 2) or 56 (experiment 1) days after fly challenge. The three cattle used in the first experiment included a 15-month-old female (No. 1), a 24–month-old female (No. 2), and a 21–month-old male (No. 3) as a control. In the second experiment, four cattle were used: two females (Nos. 4, 5) and one male (No. 6), all between 15 and 24 months of age, and one female control (No. 7) of similar age. In all the infected animals, dilation of both the sinusoids and microvasculature was apparent, as was an increase in the thickness of the extracellular matrix between the pituitary lobules. Trypanosomes were found in the microvasculature of the adenohypophysis and neurohypophysis in all the infected animals. Focal degenerative changes were seen in the adenohypophyseal section of glands from the infected animals euthanatized 56 days post-infection. These degenerative structural changes were confined to the somatotrophs cells. The possible role that trypanosomes in the microvasculature may play in inducing pituitary damage and dysfunction is discussed.